Evaluating Digital Public Service Performance of Palembang Government Websites A Usability and Citizen Satisfaction Perspective - Bella Paramitha; Indah Rahma Sari (PT. Altaf Publishing Corp, 2026)
The rapid development of digital governance has transformed the way governments deliver public services to citizens. In Indonesia, local governments are increasingly adopting web-based platforms to improve administrative efficiency, service accessibility, transparency, and public participation. Palembang City, as one of the largest metropolitan regions in South Sumatra, has implemented several digital public service websites to support municipal administration and citizen interaction. These digital platforms include civil registration services, licensing systems, public complaint portals, and public information services. Despite these technological advancements, many challenges remain regarding usability, accessibility, information quality, responsiveness, and citizen satisfaction. This study aims to evaluate the quality performance of Palembang public service websites using the System Usability Scale (SUS) integrated with the E-Government Service Quality framework This research applies a quantitative descriptive evaluation method involving 120 respondents consisting of citizens who actively use municipal public service websites. Data collection was conducted through questionnaires, direct observation, structured interviews, and system performance testing. The evaluation focuses on five main quality dimensions: usability, information quality, responsiveness, accessibility, and citizen satisfaction. Statistical analysis includes reliability testing, usability score calculation, descriptive interpretation, and comparative evaluation The results indicate that the average usability score of Palembang public service websites reached 72.4, categorized as “Good” according to SUS standards. Information quality received a score of 84.1%, responsiveness scored 79.5%, accessibility achieved 81.2%, and citizen satisfaction reached 80.6%. However, several weaknesses remain, particularly related to interface consistency, mobile optimization, and delayed service feedback mechanisms. The study concludes that while Palembang’s digital public services demonstrate acceptable performance, further improvement is required to achieve higher citizen trust and digital governance maturity.